Arti Penting Mandatory Access Consular Notification dalam Hubungan Konsuler - Anna Anindita Nur Pustika (Jurnal Hukum Lex Generalis, 2022)
One of the relationships that can be done between countries is through consular relations. Consular relations can be carried out if there is an agreement between the two parties which is then continued by sending representatives of his country to be placed in the receiving country. One of the obligations of the receiving state and the sending state is to provide protection of citizens who face legal problems in the receiving country. This is called the Mandatory Access Consular Notification, that the receiving state shall immediately notify the consular representative of the country of origin if there is a citizen of that country facing legal problems and the consular representative is obliged to provide assistance on the territory of the receiving State within the limits permitted by the law of the receiving State and international law.